THE GROWTH OF MILKFISH (CHANOS CHANOS FORSSKÃ¥L, 1775) LARVAE FROM SEVERAL HATCHERIES FOR PRODUCTIVITY SUPPORT FOR DEVELOPMENT CULTURE IN THE POND - Dharma, Tony Setia; Wibawa, Gigih Setia; Alit, AA Ketut; Aslianti, Titiek (Aquacultura Indonesiana, 2020)
The study was conducted using hafa with a volume of 1 m³ in a pond. The purpose of this study was to obtain information about the growth of second generation milkfish fry (G2), HSRT fry and wild fry  that are kept controlled in hafa on ponds. The seeds used in this study were from G2, HSRT and and wild fry with a total length (TL) about 1.5-2.0 cm. Stocking density of seeds as 250 individuals/m³. The study was conducted for 3 months until the seeds reached a total length (TL) around 10.0-12.0 cm. The treatments in this research activity were (A) G2 of seeds, (B) HSRT of seeds and (C) wild of seeds. The research activities were carried out using RAL each treatment was repeated 3 times. The feed provided is in the form of commercial pellets with a protein content of around 28-30%, with a dosage of about 5-8% biomass /day and given until full/adlibitum in the morning and evening.The results showed that the fish of G2 milkfish produced better survival rate (SR) and growth (GR) in the amount of 20-25% when compared to seeds from HSRT (B) and did not different from wild seeds (C). Survival rate and growth produced were 90.20 ± 2.60%, total length of 12.80 ± 2.40 cm and weight of 35.20 ± 2.70 g. Performance of seed produced from each treatment consists of 4 sizes, they are large (size A), medium (size B), small (size C) and very small (size D) with an average percentage of A) 25.10%, 67.10 %, 5.20% and 2.60%, B) 17.50%, 69.30% and 9.10%, 4.10% and C) 21.50%, 71.40%, 8.10% and 3.80%.This study aims to obtain information about the growth of second-generation milkfish fries (G2), HSS fries and wild fries that were farmedinhapa net. The study was conducted using hapa net with a volume of 1 m³ in a pond.The larvaeused in this study were from G2, Small schale hatchery (HSSand wild fry with a total length (TL)about 1.5-2.0 cm. The larvae were stocked with a density of 250 individuals / m³The study was conducted for three months until the larvae reached fingerling size with total length (TL) around 10.0-12.0 cm. The treatments were (A) G2 of larvae, (B) HSSRT of larvae and (C) wild of larvae. The research was carried out using Randomize Completely Design (RCD), and each treatment was repeated three times. The observed of growth for leng and weight every two weeks.The feed providedwas commercial feed in the form of pellets with a protein content of 28-30%, deliveredtwo time in the morning and evening with a dose of 5-8% biomass/days.The results showed that the fish of G2 milkfish test analysis were different significant (P<0.05),  produced better survival rate (SR) and growth (GR) in the amount of 20-25% when compared to seeds from HSS(B) and did not differentsignificant (P>0.05) from wild seeds (C). The best of Ssurvival rate and growth produced was treatment at from of G2 fry were 90.20 ± 2.60%, total length of 12.80 ± 2.40 cm and weight of 35.20 ± 2.70 g. Performance ofseed produced from each treatment consists of 4 sizes, they are large (size A), medium (size B), small (size C) and very small (size D) with an average percentage of A) 25.10%, 67.10 %, 5.20% and 2.60%, B) 17.50%, 69.30% and 9.10%, 4.10% and C) 21.50%, 71.40%, 8.10% and 3.80%.